2005
DOI: 10.1590/s1415-47572005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Association between reproductive traits and four microsatellites in Brangus-Ibagé cattle

Abstract: The aim of the present study was to verify associations between reproductive efficiency and four microsatellite markers located in synteny with genes involved in the regulation of reproductive mechanisms. A sample of 107 females from a Brangus Ibagé population (5/8 Aberdeen Angus x 3/8 Nelore) was characterized for ETH225 (D9S1) and MM12E6 (D9S20) microsatellites, mapped on chromosome 9, and HEL5 (D21S15) and AFZ1 (D21S37) on chromosome 21. Associations between the genetic markers and reproductive efficiency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
14
1
1
Order By: Relevance
“…The higher variability in STR systems observed in Brangus Ibagé as compared to the other two 682 Bovine LEPR gene polymorphisms breeds probably results from its crossbreeding composition. High levels of STR genetic diversity in the BI herd has already been described (Almeida et al, 2003(Almeida et al, , 2007Duarte et al, 2005;Oliveira et al, 2005). The Charolais herd presented the highest variability concerning the T945M polymorphism.…”
Section: Discussionmentioning
confidence: 80%
“…The higher variability in STR systems observed in Brangus Ibagé as compared to the other two 682 Bovine LEPR gene polymorphisms breeds probably results from its crossbreeding composition. High levels of STR genetic diversity in the BI herd has already been described (Almeida et al, 2003(Almeida et al, , 2007Duarte et al, 2005;Oliveira et al, 2005). The Charolais herd presented the highest variability concerning the T945M polymorphism.…”
Section: Discussionmentioning
confidence: 80%
“…In our study, we observed an increase in minor spermatozoa defects in bulls carrying a longer AFZ1 allele (121 and 127 bp) compared to animals carrying the short allele (113 and 119 bp). Oliveira et al (2005) evaluated the AFZ1 marker in a herd of Ibagé cows and found a significant effect from the favorable genotypes for AFZ1 microsatellites compared to a lower calving interval. In addition, the presence of the AFZ1 allele showed an association with beef cow pregnancy rates when fixed-time artificial insemination was used (OLIVEIRA et al, 2005;SILVEIRA et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2005) evaluated the AFZ1 marker in a herd of Ibagé cows and found a significant effect from the favorable genotypes for AFZ1 microsatellites compared to a lower calving interval. In addition, the presence of the AFZ1 allele showed an association with beef cow pregnancy rates when fixed-time artificial insemination was used (OLIVEIRA et al, 2005;SILVEIRA et al, 2013). These results demonstrate a significant association between the markers associated with IGF-IR and the reproductive performance of beef cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al (2005) relatam associações entre genótipos favoráveis para os marcadores HEL5 e AFZ-1 associados ao gene do receptor para o IGF-1 (IGF-1R) e desempenho reprodutivo. Weimer et al (2007) No presente trabalho, buscou-se uma associação entre a taxa de natalidade em vacas de corte Aberdeen Angus e marcadores moleculares e polimorfismos em genes relacionados à reprodução, como IGF1-R, LHβ, Leptina, FSHR e LHR.…”
unclassified